Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/19393210.2013.777799
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in raw cow and ewe milk from north-east Iran

Abstract: The presence of toxic metals in milk may create significant health problems for the population. In this study, 1440 raw cow and ewe milk samples from 18 townships in north-east Iran were analysed in four different seasons. Lead, cadmium and mercury levels were determined using atomic absorption spectrophotometry. Mean concentration of lead, cadmium and mercury in cow milk samples was 12.9 ± 6.0, 0.3 ± 0.3 and 3.1 ± 0.3 ng g⁻¹, respectively, and in ewe milk samples, these mean values were 14.9 ± 7.8, 1.6 ± 1.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 23 publications
2
22
2
3
Order By: Relevance
“…It also warns them to pay more attention to analysis of materials, especially the amount of pollutants, while feeding the cattle so that they would be able to minimize gastrointestinal and breathing absorption of metals such as lead and cadmium as much as possible. One study in Khorasan-e-Razavi province, north east of Iran, Najar nezhad et al reported that lead and cadmium concentrations in milk was 0.3 ± 0.3 ng/g and 0.6 ± 12.9 ng/g respectively (17). Using the atomic absorption method, Shakerian et al stated the average concentration of lead and cadmium in the raw milk gathered in Isfahan as 0.25 ppm and 0.03 ppm (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also warns them to pay more attention to analysis of materials, especially the amount of pollutants, while feeding the cattle so that they would be able to minimize gastrointestinal and breathing absorption of metals such as lead and cadmium as much as possible. One study in Khorasan-e-Razavi province, north east of Iran, Najar nezhad et al reported that lead and cadmium concentrations in milk was 0.3 ± 0.3 ng/g and 0.6 ± 12.9 ng/g respectively (17). Using the atomic absorption method, Shakerian et al stated the average concentration of lead and cadmium in the raw milk gathered in Isfahan as 0.25 ppm and 0.03 ppm (21).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, one of the reasons for the differences in allowable values of lead and cadmium in different studies was the standard rates of lead and cadmium in studied Codex (Codex international food standards). According to Codex 2000, the standard limit of lead in milk was 1000 ppb but at 2007, this limit reduced to 20 ppb, respectively (17,(21)(22)(23)26). According to results of this study, the rates of these heavy metals in the milk samples in Zabol city were much less than the global standard limits.…”
Section: Discussionmentioning
confidence: 99%
“…Także w mleku krowim z północno-wschodniego Iranu średnia zawartość kadmu była znacznie niż-sza (0,0003 ± 0,0003 mg/kg). Podobne spostrzeżenia dotyczą porównania stężenia Cd w próbkach mleka owczego, gdzie w przytoczonych badaniach średnia jego zawartość kształtowała się na poziomie znacznie niższym -0,0016 ± 0,0012 mg/kg [Najarnezhad, Akbarabadi 2013]. Według Rahimi [2013], średnia zawartość kadmu w mleku pozyskiwanym również na terenie Iranu kształtowała się na wyższym poziomie (ok. 0,002 mg/l) niż wartości wskazane przez Najarnezhad i Akbarabadi [2013].…”
Section: Wyniki I Dyskusjaunclassified
“…W mleku pozyskanym w państwie azjatyckim, a mianowicie na terenie Iranu, oznaczono bardzo zbliżone zawartości ołowiu do wartości uzyskanych w badaniach własnych. Średnie stężenie Pb wynosiło odpowiednio dla mleka krowiego i owczego 0,0129 ± 0,006 mg/kg; 0,0149 ± 0,0078 mg/kg [Najarnezhad, Akbarabadi 2013]. Średnia zawartość ołowiu w mleku, według innego autora z tego samego kraju, kształtowała się na poziomie 0,00951 mg na litr mleka, przy czym odpowiednio w mleku krowim, kozim i owczym: 0,00988 mg/l, 0,00737 mg/l, 0,0121 mg/l [Rahimi 2013].…”
Section: Wyniki I Dyskusjaunclassified
See 1 more Smart Citation